Effects of acute stress on social behavior in women - Dawans, Bernadette von; Ditzen, Beate (Psychoneuroendocrinology, 2019)
Acute stress is known to increase prosocial behavior in men via a "tend-and-befriend" pattern originally proposed as a specifically female stress response alongside the fight-or-flight response. However, the direct effects of acute stress on women’s social behavior have not been investigated. Applying the Trier Social Stress Test for groups (TSST-G), 94 women were confronted with either a stress or control condition. We repeatedly measured their subjective stress responses, salivary cortisol, and heart rate, and investigated their level of trust, trustworthiness, sharing, punishment and non-social risk using social decision paradigms. We detected significant increases in all stress parameters, as well as the wish for closeness during the stress condition. Acute stress exposure elevated prosocial trustworthiness and sharing without affecting non-social risk behavior. These results are in line with findings on the effects of stress in men, and further validate the tend-and-befriend pattern as one possible behavioral response during stress in humans.